MIND Plug-in: Development of an Electronic Medical Record based data collection tool for research in autism and neurodevelopmental disorders - Pulmano, Christian E (Archīum Ateneo, 2019)
This paper describes the efforts to support capacity building efforts for conducting research in autism in the Philippines. The objective is to adapt the SHINE OS+, an existing EHR in the Philippines, to research in autism by enabling data collection on medical profiles and diagnostic testing. The methodology follows an agile iterative approach in the design and development of the plug-in. SHINE OS+ platform is developed in PHP using the Laravel Framework. The same framework was used for the MIND plugin. Design and development stage followed post-discussion activities in the data gathering stage. Functional and non-functional requirements were identified based on user stories gathered from the stakeholders. More specific functional requirements were obtained for the following forms: Patient History, Initial Assessment, Physical Examination, ADOS-2, and Griffiths III. A three stage process is recommended to develop a customized patient management system: (1) Extraction of user stories functional and non-functional requirements to be included, (2) Inclusion of diagnostic and developmental tools, and (3) Incorporate user workflow for seamless and efficient use of the system. Open source systems like SHINE OS+ allows for the iterative development of patient management systems that are flexible to adapt to multi-users, implementing a holistic approach in understanding patients.